The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1080/14693062.2016.1164658
|View full text |Cite
|
Sign up to set email alerts
|

Compliance of the Parties to the Kyoto Protocol in the first commitment period

Abstract: International audienceThis article provides an ex post analysis of the compliance of the Parties to the Kyoto Protocol during the first commitment period (2008-2012) based on the final data for national GHG emissions and exchanges in carbon units that became available at the end of 2015. On the domestic level, among the 36 countries that fully participated in the Kyoto Protocol, only nine countries emitted higher levels of GHGs than committed and therefore had to resort to flexibility mechanisms. On the intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(50 citation statements)
references
References 19 publications
0
48
0
2
Order By: Relevance
“…Another important source of demand for carbon credits came from governments of countries—most notably Japan—that required them for compliance under the KP. Indeed, the analysis of the final data for national GHG emissions and exchanges in carbon units during the first KP Commitment Period demonstrated that overall, the Annex B parties to the KP surpassed their aggregate commitment and that all individual countries were in compliance, with 9 of 36 countries—Austria, Denmark, Iceland, Japan, Lichtenstein, Luxembourg, Norway, Spain and Switzerland—achieving it only thanks to the use of flexibility mechanisms (Shishlov et al, ). This source of demand was estimated to be around 300 million tCO 2 e between 2008 and 2015 (Bellassen et al, ).…”
Section: Fragmentation Of Carbon Markets In 2012–2014mentioning
confidence: 99%
“…Another important source of demand for carbon credits came from governments of countries—most notably Japan—that required them for compliance under the KP. Indeed, the analysis of the final data for national GHG emissions and exchanges in carbon units during the first KP Commitment Period demonstrated that overall, the Annex B parties to the KP surpassed their aggregate commitment and that all individual countries were in compliance, with 9 of 36 countries—Austria, Denmark, Iceland, Japan, Lichtenstein, Luxembourg, Norway, Spain and Switzerland—achieving it only thanks to the use of flexibility mechanisms (Shishlov et al, ). This source of demand was estimated to be around 300 million tCO 2 e between 2008 and 2015 (Bellassen et al, ).…”
Section: Fragmentation Of Carbon Markets In 2012–2014mentioning
confidence: 99%
“…Despite the positive achievements reached globally during the first commitment period of the Kyoto Protocol [64], overall the KP has been found to be more symbolic than substantive in delivering conditions for countries and industries alike and does not address the considerable variation in the emissions already produced by countries and various industrial sectors [48,65,66]. This shortfall further complicates the efforts to generate an appropriate collaborative environmental response [30,67,68].…”
Section: Fragmentationmentioning
confidence: 99%
“…While Kyoto was 'legally binding' and did include a novel compliance mechanism, the threat of enforcement was not thought to be credible. While many states may meet their targets (and most did), many believed this would largely be due to factors external to the agreement, not the risk of being punished (Rosen, 2015;Shishlov et al, 2016). Ultimately, little stood in the way when a country, like Canada, failed to meet its obligations and simply exited the treaty.…”
Section: Kyoto: the Emergence Of A Legalized Regulatory Modelmentioning
confidence: 99%